PREFERENSI MUSUH ALAMI Coccinella sp TERHADAP SIRUP TUMBUHAN BERBUNGA - Chaeriyah, Naeilul; Desriani, Desriani; Okasa, Andi Muliarni; Sulaiman, Sulaiman (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
The need for rice as one of the main food sources increases along with the population of Indonesia. One of the obstacles to increasing rice productivity is pest attacks. In the rice fields, there are predatory insects which are important as pest control agents in rice plants. Coccinella sp is a type of predator that is often found in rice plantations. The urgency of this research is the need to conserve natural enemies such as managing flowering plants and providing additional food (supplements) to predators. This is because planting flowering plants in rice fields will hinder or disrupt farmers' roads and if flowering plants are not managed properly they will become nesting places for mice, so it would be better to formulate these flowering plants into artificial syrup. This study aimed to determine the preferences of insect predators for various forms of pellets and various types of flowers. The treatments in this study were kenikir and Zinnia (Zinnia elegans). In each experiment, all treatments were put into a petri dish and a predatory imago, Coccinella sp., was released in the middle. From testing the predator response of Coccinella sp. for Kenikir and Zinnia flower syrup which were rated the best by observing the average frequency of Coccinella sp. attending each treatment with the length of time used. The experiment was arranged using a completely randomized design (CRD) treated with ANNOVA. The results showed that the response of the natural enemy Coccinella sp. frequency of visits was most often to white Zinnia flower syrup which was sweetened with brown sugar solution and the longest was to yellow kenikir flower syrup which was added to honey solution.